Numerical analysis of nonlinear fractional Klein–Fock–Gordon equation arising in quantum field theory via Caputo–Fabrizio fractional operator - Prakash, Amit; Kumar, Ajay; Baskonus, Haci Mehmet; Kumar, Ashok (Mathematical sciences (Karaj, Iran), 2021)
The present article deals with the solution of nonlinear fractional Klein–Fock–Gordon equation which involved the newly developed Caputo–Fabrizio fractional derivative with non-singular kernel. We adopt fractional homotopy perturbation transform method in order to find the approximate solution of fractional Klein–Fock–Gordon equation in the form of rapidly convergent series. Existence and uniqueness analysis of the considered model is provided. We consider few numerical examples to validate the projected technique. The obtained results shows that this method is very efficient, simple in implementation and that it can be applied to solve other nonlinear problems.